In situ forming hydrogel recombination with tissue adhesion and antibacterial property for tissue adhesive. (July 2022) - Zhang, Wenjie; Jiang, Yongchao; Wang, Haonan; Li, Qian; Tang, Keyong
In situ forming hydrogels with strong adhesive strength and antibacterial activity are of great interest to serve as tissue adhesive in fields like wound dressing and mass hemorrhage. In this study, hybrid hydrogel (GOHA) based on gelatin and oxidized hyaluronic acid was developed and endowed with excellent mechanical strength and tissue adhesion. According to our results, GOHA hydrogel exhibits a fast gelation time of around 60 s, robust compression strength of 223.43 ± 24.28 kPa, and strong adhesion of 14.33 ± 0.78 kPa to porcine skin, which is much higher than that of commercial fibrin glue (around 1.00 kPa). Meanwhile, through the loading of levofloxacin, obvious antibacterial activity can be obtained for wider applications. Notably, it would not compromise the hemocompatibility and cytocompatibility in vitro. In summary, this kind of hybrid hydrogel shows great potential as tissue adhesive in biomedical fields.